Evolution of blood biomarker levels following percutaneous atrial septal defect closure in adults. (October 2020) - Geenen, Laurie W.; Uchoa de Assis, Lucas; Baggen, Vivan J.M.; Eindhoven, Jannet A.; Cuypers, J.A.A.E.; Boersma, Eric; Roos-Hesselink, Jolien W.; van den Bosch, Annemien E.
Highlights: A substantial number of adults with unrepaired ASD have elevated biomarker levels. Percutaneous ASD closure in adults leads to acute changes in most biomarker levels. TnT, CRP, RDW, GDF-15 increase immediate after ASD closure and galectin-3 decreases. Long-term reverse cardiac remodeling was not reflected by a decrease in biomarkers. Novel biomarkers can help to elucidate mechanisms of reverse cardiac remodeling. Abstract: Background: We sought to assess the effects of percutaneous atrial septal defect (ASD) closure on blood biomarker levels that possibly reflect reverse cardiac remodeling. Therefore, this study investigated temporal changes in six blood biomarkers following percutaneous ASD closure in adults. Methods: In this prospective observational cohort study, adults with ASD type II scheduled for percutaneous closure were included (2012–2016). NT-proBNP, high-sensitive troponin-T (hs-TnT), high-sensitive C-reactive protein (hs-CRP), red blood cell distribution width (RDW), growth differentiation factor-15 (GDF-15) and galectin-3 were measured one day prior to ASD closure and one day, three months and one year post ASD closure and changes were evaluated using paired T-tests. Echocardiographic measurements were obtained. Results: Fifty patients were included (median age 50 years, 62% women, 32% NYHA II). At baseline, biomarker levels were elevated in a substantial number of patients; NT-proBNP n = 22 (45%), hs-TnT n = 6 (13%) hs-CRP n = 19 (40%), galectin-3n = 5 (11%) and GDF n = 10 (23%). One day after ASD closure, significant increases of hs-TnT (median change (Δ) = 12 ng/L), hs-CRP (Δ = 1.9 mg/L), GDF-15(Δ = 129 pg/mL) and RDW (Δ = 0.1%) were observed, and a decrease in galectin-3 (Δ = −1.0 ng/mL). Consequently, 92% had at least one abnormal biomarker directly after closure. At three months biomarker levels returned to baseline, and while echocardiographic measures 1 year post closure were indicative of reverse cardiac remodeling, biomarker levels did not further decrease. Conclusion: Percutaneous ASD closure in adults leads to a direct increase in most blood biomarkers, in particular hs-CRP and hs-TnT. After three months, biomarkers returned to baseline levels and remained stable up to one year.